Bridging vision gaps: a comprehensive study of the RAAHI programme for improving truckers’ eye health in India - Sahu, Ananta Basudev; Tiwari, Jatin; P. N., Prasannakumar; Mohanty, R. N. (International Journal Of Community Medicine And Public Health, 2024)
Background: Visual impairment presents a significant public health concern globally, with a notable impact on individuals’ quality of life. Despite efforts to address this issue, unmet eye health needs persist, particularly in vulnerable populations such as truck drivers in low and middle-income countries like India. The RAAHI (National truckers eye health programme) initiative aims to fill this gap by providing essential eye care services in India. Methods: This research manuscript delves into the journey of the RAAHI programme from 2017 to 2022, assessing its achievements, challenges, and lessons learned. A mixed-methods approach involving a secondary review of literature, programme records, and stakeholder interactions was employed. Quantitative analysis of beneficiary demographics and service utilization trends was complemented by qualitative insights from beneficiary feedback and stakeholder interviews. Results: RAAHI demonstrated a significant presence across 54 locations, screening over 540,000 beneficiaries between 2018 and June 2022. The programme primarily targeted truck drivers, addressing their unmet eye health needs and raising awareness about prevalent health conditions. Beneficiary feedback highlighted overall satisfaction with RAAHI services, emphasizing the programme’s structured approach and immediate access to quality spectacles. Furthermore, qualitative analysis suggests RAAHI’s success enriching the programme’s effectiveness and client-centric approach. Conclusions: These findings offer valuable insights into addressing visual impairment among vulnerable populations and advocating for the integration of eye care into public health initiatives. Additionally, the study highlights the importance of sustained efforts and collaborative partnerships in ensuring the success and scalability of programmes like RAAHI.